Analisis Sistem Kinerja SIAKAD untuk Pembayaran SPP Mahasiswa pada STMIK Widuri dengan Metode PIECES - Veronika Natalia; Nur Nawaningtyas Pusparini; Sandri Sagitarius Sarumaha (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
This research analyzes the performance of the Academic Information System (SIAKAD) in supporting student tuition payments at STMIK Widuri using the PIECES method (Performance, Information, Economy, Control, Efficiency, Service). SIAKAD aims to streamline academic administration and enable online payments. However, issues such as system access delays, especially near payment deadlines, still occur, negatively impacting students' academic services and resulting in administrative penalties. The study employed data collection techniques through observation, interviews, questionnaires, and literature review. The PIECES framework was applied to evaluate six key indicators: performance, information, economy, control, efficiency, and service. The findings reveal that all indicators achieved an average score above 3.80, indicating a "good" system performance. Nonetheless, further improvements are necessary, particularly in terms of access speed and data security, to minimize user difficulties. The study concludes that optimizing the SIAKAD system is crucial for achieving effective and efficient payment processes. Recommendations include enhancing service quality, improving information accuracy, and strengthening data security. This optimization is expected to increase user satisfaction and support the institution's financial management stability.